Dinamika Kekuasaan dan Praktik Penyusunan Anggaran Pendapatan dan Belanja Daerah (APBD) - Febry Maharani, Annisa; Alfiandi, Bob; Afrizal, Afrizal (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research analyzes the dynamics of bureaucratic contestation in the process of formulating the Regional Revenue and Expenditure Budget (APBD). Using the perspective of bureaucratic pluralism, this study explores how various actors with diverse interests compete to influence budget allocation. This descriptive qualitative research collects data through in-depth interviews with key stakeholders and analysis of official documents. The results reveal that the APBD formulation process involves tension between technocratic and political aspects, where contestation occurs at various levels between Regional Apparatus Organizations (OPD), between divisions within OPD, and between executive-legislative bodies. Technocratic aspects that should prioritize rationality and objectivity are often subordinated by political interests and power relations. Success in obtaining budget allocations is determined not only by planning quality and supporting data but also by interpersonal relationships and political affiliations. The high fiscal dependence on transfer funds from the central government (reaching 95%) indicates weak regional independence and limits budget innovation space. This study also finds marginalization of community aspirations in the participatory planning process, where many community proposals from Development Planning Forums (Musrenbang) are not accommodated due to budget constraints, domination of political interests, or weak advocacy. This research contributes to the development of public administration literature by providing a comprehensive understanding of the interaction between bureaucracy, politics, and society in the context of fiscal decentralization in Indonesia, and offers practical implications for improving the effectiveness of regional budget allocation.